PENDUGAAN KARBON TERSIMPAN PADA PERMUKAAN TANAH DI BERBAGAI JALUR HIJAU KECAMATAN BANJARBARU UTARA KOTA BANJARBARU - Danial Danial; Wahyuni Ilham; Mufidah Asy'ari (Jurnal Sylva Scienteae, 2020)
Most contributors to carbon dioxide are generally in urban areas this is due to pollution from motorized vehicles and industries that produce large amounts of carbon dioxide. The problem of carbon in urban areas can be overcome by building a green open space one of them by creating a green lane. The existence of green lines plays a role in efforts to increase  absorption through photosynthesis, the photosynthesis results, among others are stored in the form of biomass which makes the vegetation grow to be larger or higher. This study aims to identify plant species in the green line and analyze the potential of biomass and carbon stored in the green path of the northern banjarbaru sub-district. Based on observational data in the field there are 13 types of plants that grow in the green lane of the northern banjarbaru sub-district and the type grows the most is the type of angsana (Pterocarpus indicus) as many as 98 plants. The overall biomass content is 3606.36 tons/ha while the stored carbon content is 1474.92 tons/ha.Key words: Biomass, Carbondioxide